Drugs and Clinical Approaches Targeting the Antiapoptotic Protein: A Review. (29th September 2019) - Han, Zeping; Liang, Jiening; Li, Yuguang; He, Jinhua
Abstract : B-cell lymphoma 2 (Bcl-2) is a regulator protein involved in apoptosis. In the past few decades, this protein has been demonstrated to have high efficacy in cancer therapy, and several approaches targeting Bcl-2 have been tested clinically (e.g., oblimersen, ABT-737, ABT-263, obatoclax mesylate, and AT-101). This review reports potential Bcl-2 inhibitors according to current information on their underlying mechanism and the results of clinical trials. In addition, the function and mechanisms of other potentially valuable Bcl-2 inhibitors that did not show efficacy in clinical studies are also discussed. This summary of the development of Bcl-2 inhibitors provides worthwhile viewpoints on the use of biomedical approaches in future cancer therapy.